2018
DOI: 10.1111/jen.12531
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiastrains, and lack of genetic diversity and parthenogenesis in Brazilian populations ofTuta absoluta(Lepidoptera: Gelechiidae)

Abstract: The pheromone‐based control of the invasive tomato pinworm Tuta absoluta (Lepidoptera: Gelechiidae) has been unsatisfactory in some cases, and parthenogenesis was reported in this species. As the parthenogenesis phenomena is a shortcoming that compromises the pheromone‐based control of T. absoluta and that is potentially explained by the occurrence of the endosymbiont Wolbachia in this pest species, the objectives of this study were (i) to survey the Wolbachia strains in Brazilian pinworm populations, (ii) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
7
9
1
Order By: Relevance
“…Most Wolbachia infecting lepidopteran insects belong to supergroup A or B, and most of them belong to supergroup B [ 65 , 66 ]. In the current study, the Wolbachia detected in the three different geographical populations of T. absoluta appeared to belong to supergroup B, which was consistent with previous results in a Brazilian population and Iranian and Turkish populations [ 67 , 68 ].…”
Section: Discussionsupporting
confidence: 92%
“…Most Wolbachia infecting lepidopteran insects belong to supergroup A or B, and most of them belong to supergroup B [ 65 , 66 ]. In the current study, the Wolbachia detected in the three different geographical populations of T. absoluta appeared to belong to supergroup B, which was consistent with previous results in a Brazilian population and Iranian and Turkish populations [ 67 , 68 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other comprehensive studies about Wolbachia infection in Lepidopteran families showed 58.3% in 120 species of Siberian populations (Ilinsky and Kosterin, 2017); 45% of 49 Japanese species (Tagami and Miura, 2004); 52% of 29 Indian species (Salunke et al, 2012), and 79% of 24 Acraea species from Uganda (Jiggins et al, 2001). In our study, all tomato leaf miner populations displayed 100% of Wolbachia infection, which is consistent with the populations from Brazil, Croatia, and Montenegro (Škaljac et al, 2012;Carvalho et al, 2018). Although Wolbachia is mostly known bacteria, Spiroplasma were present at low levels while Rickettsia was also not commonly found with only one species across Lepidopterans.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the findings of high genetic homogeneity among T. absoluta populations with high prevalence of Wolbachia and Pantoea infections seems to imply that both bacterial infections have less impact on the mtDNA variations. Our results are in accordance with the findings about the populations reported in Brazil (Carvalho et al, 2018). Even though these results differ from previous studies that report that Wolbachia spread affects the mtDNA diversity of its host through indirect selection, which means if a population gains any reproductive advantage or fitness from Wolbachia, the initial mtDNA type will hitchhike through the population and change the uninfected haplotypes (Hurst and Jiggins, 2005;Schuler et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations